Peru and recurring calamities - Huertas Vallejos, Lorenzo (2018)
Our national history is plagued with records of calamities originated by nature. It was in the city of Cuzco that in the fifteenth century the very Inca Pachacútec had to undertake the reconstruction of our historical capital, it is known that in the time of the said Inca there was a Critical Lapse, one of the most severe that registers the Andean History; and it was the Inca himself who directed the reconstruction with admirable planning and using as a variable a surprising change of scale. Pachacútec with the best intelligences of his time, especially with architects like Huallpa Rimachi Inca, Inca Rimachi, Inca Cache and Calla Cunchuy. Also in that work were members of the priestly structure (yayachis) who knew how to administer nature. In this reconstruction there were also military commands that ordered the mitayos and other people that was the working mass. And they did change of scale, where they used to work ten, in the time of the Reconstruction they did it a hundred. Today we have to do the reconstruction thinking that the Children of the future are going to be stronger due to the Global Warming that is why the need for change of scale.